The fight for power: historical women’s movements of Russia and Great Britain in comparison - Hinterhuber, Eva Maria; Günther, Jana (Frontiers in Sociology, 2023)
In the second half of the 19 th century, women began to organize worldwide to achieve the goal of gender equality. National women's movements emerged and were followed somewhat later by the first transnational political mobilization of women on a larger scale (Tripp, 2006, 55). The range of topics that were on the national and international agenda included, alongside the access to education and the enforcement of equal civil rights, as well as the fight for political participation, with the women's right to vote taking center stage 1 . The political, social, and cultural contexts, in which women raised their voices, varied. On the national level, female activists often had conflicting positions and their strategies reflected a wide spectrum; the chosen forms and the course of the protest, on the other hand, showed similarities.The fight for Power: an Introduction A systematic comparison 2 of selected historical women's movements presents an opportunity to map out the differences and parallels regarding framework conditions and starting points, as well as point out the continuities and gaps between historical and current women's movements. With the early Russian and British women's movements of the turn of the century, the choice fell to two movements that were subject to unique historical and political circumstances. Therefore, we are using the "most-1 This applies not only to Great Britain, Germany, and Russia, but also to Chile, Japan, and China, to name but a few (Tripp, 2006, 55).2 This article is based on a joint research project of Jana Günther and Eva Maria Hinterhuber, which has taken its starting point in an article published in 2017 under the title "Der Kampf um Macht: Historische Frauenbewegungen in Russland und Großbritannien im Vergleich", in Femina Politica 2017(1), 24-39. In several papers, the authors discussed further questions related to the topic. The article reflects these questions and discussions. The authors would like to thank Anastasia Kappo-Klevska and Rebecca Knecht for its translation into the English version at hand and Lotta T. Barabasch for the editing. Nonetheless, any mistakes are the responsibility of the authors.